(untitled) (Third Sector Social Economic Review, 2025)
This study examines the impact of Generation Y’s attitudes towards AI on organizationalforgetting and the mediating role of psychological capital in this relationship. Data were collected through a survey of 325 Generation Y individuals working in various sectors in Istanbul. Analyses were conducted using regression and structural equation modelling methods, and the mediating effect was tested using the bootstrap method in AMOS software. The findings indicate that positive attitudes towards AI have significant and positive effects on both psychological capital and organizationalforgetting. Furthermore, psychological capital was found to play a partial mediating role in the relationship between these two variables. This result suggests that individuals’ perspectives on AI technologies strengthen not only organizationalprocesses but also employees’ psychological resources. The study emphasises that individual attitudes and psychological resources play a critical role in organizational learning and adaptation during digital transformation processes. In this context, it is suggested that strategies aimed at improving employees’ psychological capital can make significant contributions to organisations during the transition to AI applications.